PENERAPAN MODEL PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN KOLABORASI SISWA DALAM MEMBUAT KARYA SENI RUPA DI KELAS IV MI MUHAMMADIYAH BUNTU BARANA - Nur Hijrah; Arif Efendi AS; Hasan (STKIP Subang, 2026)
This study was motivated by the low level of students' collaboration skills in visual arts learning among fourth-grade students at MI Muhammadiyah Buntu Barana. Students tended to complete tasks individually, participated less actively in discussions, and were not accustomed to working effectively in groups. This study aimed to describe the implementation of the Project Based Learning (PjBL) model in visual arts learning and to examine the improvement of students' collaboration skills through its implementation. The research employed a Classroom Action Research (CAR) design using a mixed-methods approach that integrated quantitative and qualitative data. It was conducted in two cycles during a diorama-making project. The participants consisted of all 21 fourth-grade students. Data were collected through observation, interviews, and documentation, and were analyzed using quantitative analysis (mean scores and percentage of learning mastery) and qualitative analysis through data reduction, data display, and conclusion drawing. The findings revealed that students' collaboration skills improved from 38.09% in the pre-cycle to 57.14% in Cycle I and reached 85.71% in Cycle II. The improvement was reflected in students' increased participation in discussions, better task sharing, greater respect for peers' opinions, and stronger responsibility in completing group projects. It can be concluded that the implementation of the Project Based Learning (PjBL) model was effective in enhancing the collaboration skills of fourth-grade students in visual arts learning.